Pengaruh Current Ratio, Debt To Equity Ratio, Total Asset Turnover dan Net Profit Margin Terhadap Profitabilitas - Agustin Chandra Dewi; Sri Dwi Estiningrum (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to examine and determine the effect of the Current Ratio, Debt to Equity Ratio, Total Asset Turnover, and Net Profit Margin on Profitability (Return on Assets). The research uses an associative approach, and the type of data used is quantitative in the form of secondary data, which is analyzed using a financial ratio scale. The population in this research is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 periods, which are 26 companies. There were 12 manufacturing companies in the food and beverage sub-sector that met the criteria so that the sample to be used was 36. The results showed that the current Ratio had no significant effect on Return on Assets. Meanwhile, theDebt to Equity Ratio, Total Asset Turnover, and Net Profit Margin significantly affect Return on Assets. The research results will also have implications for business actors. Companies must be able to utilize their assets and capital optimally and efficiently and continuously monitor how their financial health is, primarily related to matters that can affect the company's profitability, such as related to asset management and owned capital. In order to be able to maintain the viability of the business or company.